Brown Tumor of the Mandible as an Initial Presentation of Hyperparathyroidism - Antigoni Delantoni; Merve Önder; Kaan Orhan (Ankara University, 2021)
The paper presents a brown tumor case related to secondary hyperparathyroidism in an end stage kidney disease patient undergoing dialysis treatment. The interesting feature of the case is that the primary clinical presentation of the condition was a mild swelling in the attached gingiva of a mandibular molar tooth. Medical practitioners should be alert to the fact that some pathological conditions may have an initial presentation in the oral cavity. Thus, a thorough and careful examination of the oral mucosa with the accompanying dental radiographs of patients, should be noted and studied in all cases, where available.